Differences Between Serum Total Testosterone Levels in Obese and Non-Obese Male Health Workers - Putu Ayu Indah Saraswati; Ketut Suastika; I Made Pande Dwipayana (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Obesity is a metabolic condition that poses a global health challenge and is associated with various complications, including reduced testosterone levels. Low testosterone is a critical component in metabolic syndrome and hormonal dysfunction in men. This study aims to analyze the differences in total serum testosterone levels between obese and non-obese male healthcare workers and identify factors influencing low testosterone levels at Prof. dr. I.G.N.G. Ngoerah General Hospital, Denpasar. This cross-sectional study involved 89 male healthcare workers grouped based on body mass index (BMI): obese (BMI ≥ 25 kg/m²) and non-obese (BMI 25 kg/m²). Total serum testosterone levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Statistical analysis included bivariate tests using Chi-Square and Fisher-Exact tests, followed by multivariate logistic regression to determine the relationship between obesity and low testosterone levels, adjusting for confounding factors such as age, type 2 diabetes mellitus, hypertension, and heart disease. The mean total serum testosterone level was 528.74 ± 265.13 ng/dL. The prevalence of low testosterone was significantly higher in the obese group (82.6%) compared to the non-obese group (17.4%), with an odds ratio (OR) of 13.691 (p 0.001). Multivariate analysis identified obesity as an independent predictor of low testosterone, with an adjusted odds ratio (AOR) of 6.101 (95% CI: 1.531–24.307; p = 0.010). Age was also a significant factor, with participants aged ≥30 years having a higher risk of low testosterone compared to younger participants (AOR: 4.961; 95% CI: 1.118–22.004; p = 0.035). Type 2 diabetes mellitus was strongly associated with low testosterone levels (OR: 22.909; p 0.001) but was not significant in the multivariate analysis (p = 0.060). Obesity is a significant risk factor for low testosterone levels in male healthcare workers, with age being another key determinant. These findings highlight the importance of early detection and management of obesity to prevent hormonal dysfunction. Keywords: Obesity, Total Serum Testosterone, Male Healthcare Workers.